2022
DOI: 10.1038/s41467-022-30905-4
|View full text |Cite|
|
Sign up to set email alerts
|

Eruption of ultralow-viscosity basanite magma at Cumbre Vieja, La Palma, Canary Islands

Abstract: The viscosity of magma exerts control on all aspects of its migration through the crust to eruption. This was particularly true for the 2021 eruption of Cumbre Vieja (La Palma), which produced exceptionally fast and fluid lava at high discharge rates. We have performed concentric cylinder experiments to determine the effective viscosities of the Cumbre Vieja magma, while accounting for its chemistry, crystallinity, and temperature. Here we show that this event produced a nepheline-normative basanite with the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
115
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(127 citation statements)
references
References 46 publications
9
115
2
1
Order By: Relevance
“…Seismicity bursts (Fig. 3a–d ) were shortly followed by increased lava emission and/or opening of new vents 25 , 34 , which may reflect structural instabilities resulting from increased magma withdrawal from the deep reservoir. An increase of the shallow seismicity rate by late November 2021 (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seismicity bursts (Fig. 3a–d ) were shortly followed by increased lava emission and/or opening of new vents 25 , 34 , which may reflect structural instabilities resulting from increased magma withdrawal from the deep reservoir. An increase of the shallow seismicity rate by late November 2021 (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The eruption started at 14:10 UTC along a NW-SE fissure and remained active for 85 days and 8 hours, to date the longest known eruption at La Palma. The eruption showed variable explosive behaviour 25 , with a mean eruptive column height of ~3500 m and emissions of large lava flows (12.19 km 2 ), forming 2 lava deltas on the Western coast 1 .…”
Section: Introductionmentioning
confidence: 99%
“…The density of the proximal deposit (<1.5 km from vents) was considered to estimate the density of the cone, in agreement with observations for basaltic cones at Etna volcano (Italy; e.g., McGetchin et al., 1974; Pioli et al., 2022). Lava density was determined based on the model DensityX (Iacovino & Till, 2019) and the data set of Castro and Feisel (2022) (i.e., composition, water, temperature, and pressure), resulting in a value of 2,770 ± 50 kg m −3 . This value well agrees with the density of the lava that was measured on 10 samples collected between 26 September and 6 October 2021 using a Helium Pycnometer resulting in a value of 2,618 ± 179 kg m −3 .…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, undular hydraulic jumps >5 m amplitude are reported for lava flowing at ∼15 m/s during the 2005 eruption of Sierra Negra volcano, Galapagos, Ecuador (volumetric eruption rates ∼100 m 3 /s; Geist et al., 2008; https://www.youtube.com/watch?v=W72foSDHjJg). Low viscosity (<100 Pa s) lava flows of Cumbre Vieja, La Palma, Spain (Castro & Feisel, 2022), and Nyiragongo volcano, Democratic Republic of the Congo (Giordano et al., 2007), have near‐vent velocities >5 m/s and produce thin (<∼1 m) flows that are certainly supercritical during emplacement, although proximal observations are limited and published still and video images from these eruptions (Castro & Feisel, 2022; Tazieff, 1977; Tedesco et al., 2007) lack the spatial scales necessary for our application of Equations 2 and 3, retrospectively. However, in these and future eruptions, real‐time estimates of lava effusion rates using hydraulic theory would allow rapid assessment of flow parameters for input into hazard models and forecasts of flow advance toward populated areas, such as the large and vulnerable city of Goma downslope of Nyiragongo (Chirico et al., 2009; Tazieff, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…In this paper we focus exclusively on undular hydraulic jumps, which differ from other types of standing waves in their hydraulic properties and architecture. Observations of analogous wave patterns in lava are largely anecdotal and have been reported most commonly for fast-moving Hawaiian lava flows (e.g., Dietterich et al, 2021;Finch & Macdonald, 1953;Kauahikaua et al, 1998;Macdonald, 1943;Wolfe, 1988), although they have also been described in low viscosity lava flows from La Palma (Castro & Feisel, 2022). A recent paper by Le Moigne et al (2020) suggested that open-channel hydraulic theory for hydraulic jumps, particularly those formed by changes in flow geometry, can be applied to lava flows to infer both flow dynamics and key physical properties.…”
Section: Dietterich Et Almentioning
confidence: 97%